Creative Research of The Apsornsaran Music Serieson Jazz Merge Style - Camacho, Ittikorn (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2022)
This creative research is qualitative research with the following objectives: 1) to study the society and culture of Southern Isan in the context of Apsornsaran. 2) To create “The Apsornsaran Music Series on Jazz Merge Style” in contemporary jazz music. The population used in the research were 2 Southern Isan Folk Artists and 2 Southern Isan folk music experts. The research instrument was a semi-structured interview form presenting in the descriptive information and creative works. The results showed that Southern Isan society and culture in the context of Apsararan which appears as a story that shows the value, meaning, and way of life of the Southern Isan people, through the 5 songs for the Apsararan dance performance. Which represents elegance, sweetness, and fun of the art of folk music in the south of the northeast, these are 1) Hae Hom 2) A Yai Lam Bae 3) Kaew Nor 4) Mong Kwon Jong Dai 5) Kajpaka. The results of the creation of the Apsornsaran music series found 1) The songs appear on both major and minor pentatonic scales. 2) Keys and scales are changed using cadence as a tool. 3) The Skaul drum is clearly associated with the rhythm of the melody. 4) Appears monophony, polyphony, and homophony music texture in playing and arranging. 5) The Composition and melody of Kantrum harmoniously and beautifully harmonized with jazz music. 6) Southern Isan folk musicians can harmoniously play creative songs with jazz musicians under the agreement on the western music tunning systems established by the researcher.